A model of spreading forest fires - Quang, V. D.; Nam, N. T.; Lien, H. D.; Antonov, I. S.; Krastanska, T. T. (Vietnam Journal of Mechanics, 2003)
Current article describes a mathematical model for throwing burning wood material out of a main body of fire with a help of wind. A problem is solved by numerical way and it is given some of results, which are received during numerical experiment.